FEASIBILITY AND RELIABILITY OF MUSCULOSKELETAL ULTRASOUND MEASUREMENT OF THE MEDIAL PATELLOFEMORAL LIGAMENT. Issue 4 (28th April 2020) - Stracciolini, Andrea; Boucher, Laura; Jackson, Sarah; Brown, Naomi; Magrini, Danielle; McKee-Proctor, Maxwell; d'Hemecourt, Pierre; Delzell, Patricia
Background: The medial patellofemoral ligament (MPFL) is an important soft tissue constraint to preventing patellar dislocations in young athletes. The anatomy of the MPFL has been investigated in cadaveric studies and magnetic resonance studies. No studies to date have provided anatomical data of the MPFL on ultrasonography. Purpose: To investigate the feasibility of musculoskeletal ultrasonography for the evaluation of the MPFL, and to determine interrater and intrarater reliability for MPFL ultrasound measures. Methods: Ten control participants (20 knees) 20 to 50 years underwent ultrasonography performed by 3 researchers (musculoskeletal ultrasound radiologist, athletic trainer/biomechanist, primary care sports medicine physician) from 3 different institutions for interrater reliability testing. Intrarater reliability testing was performed at 2 separate institutions by 4 physicians, each performing the same knee ultrasound protocol on 20 knees in 10 study participants 2 to 3 weeks apart. In total, 180 images were created for interrater reliability, and 480 images for intrarater reliability. Examinations were performed with linear high-frequency transducers (10-18 MHz) with the participant in the supine position and the extremity flexed at 45°. Measurements included ligament length (long axis to ligament) from the patellar to the femoral attachment sites, ligament width (short axis to ligament) at the patellar attachment, and ligament thickness (long axis to ligament) midway between the patella and femur. Mean and SD were calculated for all measurements. Intraclass correlation coefficient (ICC) analysis was used to assess intrarater and interrater reliability. ICC values < 0.40 indicated poor reliability, whereas those between 0.40 and 0.75 indicated fair to good reliability, and those > 0.75 indicated excellent reliability. Results: The mean US value for MPFL length was 44.83mm (SD 6.68), mean thickness 2.66mm (SD 0.85), and mean width 11.76mm (SD 2.99). The overall ICC values for interrater reliability testing indicated fair to good reliability for length measures (0.7) and poor reliability for thickness (–0.1) and width (0.3; Table 1.1). Overall ICC values for intrarater reliability indicated fair to good reliability for length (0.5), excellent for thickness (0.9), and poor reliability for width (–0.3; Table 1.2). Conclusions: Musculoskeletal ultrasonography is a feasible and reliable office-based method of measuring MPFL length and thickness. These quantitative measures set the groundwork for establishing normative anatomical measures of the MPFL in athletes and establish a protocol for testing and measuring the MPFL using musculoskeletal ultrasonography. : Table 1.1. Intraclass Correlation Coefficients (ICC) for testing reliability between physicians (inter-rater). ICC Length Thickness Width Overall 0.708 (0.291, 0.898) -0.047 (-0.452, 0.442) 0.253 (-0.179, 0.652) xx vs xx 0.833 (0.562, 0.937) -0.055 (-0.312, 0.309) 0.062 (-0.389, 0.498) xx vs xx 0.297 (-1.246, 0.776) -0.014 (-0.385, 0.447) 0.253 (-0.130, 0.672) xx vs xx 0.707 (0.053, 0.907) 0.032 (-2.554, 0.704) 0.286 (-0.874, 0.756) *Data analyzed using two-way mixed, absolute agreement analysis. Expected value is shown, along with lower and upper bounds of 95% confidence intervals. Table 1.2. Intraclass Correlation Coefficients (ICC) for test-retest (intra-rater) reliability among individual physicians. Length Thickness Width Overall 0.492* (0.190, 0.681) 0.858 (0.772, 0.912) -0.319 (-0.056, 0.566) Physician 1 0.589 (-0.024, 0.842) 0.400 (-0.300, 0.754) 0.386 (-0.241, 0.756) Physician 2 0.014 (-0.393, 0.447) 0.260 (-0.965, 0.722) -0.097 (-0.683, 0.432) Physician 3 -0.085 (-2.104, 0.604) 0.463 (-0.228, 0.786) -1.910 (-7.683, -0.027) Physician 4 0.792 (0.467, 0.918) 0.634 (0.053, 0.857) -0.224 (-1.272, 0.435) *Data analyzed using two-way mixed, absolute agreement analysis. Expected value is shown, along with lower and upper bounds of 95% confidence intervals.